Oscillatory Mixed Convection in a Porous Medium - S.K Ghosh (Journal of Applied Fluid Mechanics, 2014)
Oscillating mixed convection on the fully developed flow between two infinitely long vertical walls heated asymmetrically in a porous medium, has been studied. It experiences g -jitter force associated with microgravity in the field of space science with reference to crystal growth in space. Our present study can be exposed to a real life situation of a microgravity field. The time varying gravity field generates oscillatory free convection velocity field. This is combined with the forced oscillating flow driven by a pressure gradient.